Bridging the Gap: Modulatory Roles of the Grb2-Family Adaptor, Gads, in Cellular and Allergic Immune Responses - Yablonski, Deborah (Frontiers in Immunology, 2019)
Antigen receptor signaling pathways are organized by adaptor proteins. Three adaptors, LAT, Gads and SLP-76, form a heterotrimeric complex that mediates signaling by the T cell antigen receptor (TCR) and by the mast cell high affinity receptor for IgE (FcεRI). In both pathways, antigen recognition triggers tyrosine phosphorylation of LAT and SLP-76. The recruitment of SLP-76 to phospho-LAT is bridged by Gads, a Grb2 family adaptor composed of two SH3 domains flanking a central SH2 domain and an unstructured linker region. The LAT-Gads-SLP-76 complex is further incorporated into larger microclusters that mediate antigen receptor signaling. Gads is positively regulated by dimerization, which promotes its cooperative binding to LAT. Negative regulation occurs via phosphorylation or caspase-mediated cleavage of the linker region of Gads. FcεRI-mediated mast cell activation is profoundly impaired in LAT- Gads- or SLP-76-deficient mice. Unexpectedly, the thymic developmental phenotype of Gads-deficient mice is much milder than the phenotype of LAT- or SLP-76-deficient mice. This distinction suggests that Gads is not absolutely required for TCR signaling, but may modulate its sensitivity, or regulate a particular branch of the TCR signaling pathway; indeed, the phenotypic similarity of Gads- and Itk-deficient mice suggests a functional connection between Gads and Itk. Additional Gads binding partners include costimulatory proteins such as CD28 and CD6, adaptors such as Shc, ubiquitin regulatory proteins such as USP8 and AMSH, and kinases such as HPK1 and BCR-ABL, but the functional implications of these interactions are not yet fully understood. No interacting proteins or function have been ascribed to the evolutionarily conserved N-terminal SH3 of Gads. Here we explore the biochemical and functional properties of Gads, and its role in regulating allergy, T cell development and T-cell mediated immunity.